Analisis Perhitungan Harga Pokok Produksi Dengan Menggunakan Metode Full Costing Pada Umkm Bakso Keliling - Alda; Nurhayati; Maharani, Eka Fira (PT Maju Malaqbi Makkarana, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector, especially the meatball business, face complex challenges in financial management and product pricing. This study aims to analyze the calculation of the cost of goods manufactured (HPP) in meatball SMEs using the full costing method. The focus of the study is to identify the cost structure that includes raw materials, direct labor, and factory overhead costs to improve the accuracy of selling price determination and business profitability. The study uses a qualitative approach with interviews, observations, and secondary data analysis from related documents and literature. The results of the study show that the total daily production cost is IDR 1,509,680 for 1,200 meatballs, with a production cost per item of IDR 1,258. With a selling price of IDR 2,000 per item, the net profit obtained reaches IDR 890,320 or IDR 741 per item. This finding emphasizes the importance of accurate cost management to maintain business efficiency and competitiveness. This study concludes that the full costing method provides a comprehensive picture for strategic decision making, including setting competitive selling prices. Recommendations include analysis of ongoing costs, product innovation, aggressive marketing strategies, and investment in equipment and employee training to improve business performance and profitability. The study suggests an analysis of the importance of ongoing costs, product innovation, aggressive marketing strategies, and investment in equipment and human resource development. This study provides theoretical contributions to the understanding of cost accounting in culinary sector MSMEs and offers managerial practices that can improve business performance and profitability.